The effect of executive functions on word reading among students with Chinese as a second language (CSL) - Cai, Mingjia; Liao, Xian (Studies in Second Language Learning and Teaching, 2025)
Executive functions (EF) have long been recognized as critical factors in accounting for individual differences in literacy development. However, their role in second language (L2) learning, particularly in non-alphabetic languages such as Chinese, has not been fully explored. This study endeavored to examine the role of EF in word reading among 200 Chinese as a second language (CSL) learners in Hong Kong. Participants completed a series of tasks measuring EF components, including inhibition, visual working memory, verbal working memory, and cognitive shifting, as well as tasks assessing their word reading abilities, which encompassed both single-character reading and two-character word reading. The contributions of EF to the total word reading score, single-character reading, and two-character word reading were analyzed. The results demonstrated that visual working memory and inhibition emerged as unique and significant predictors. Moreover, EF explained a greater proportion of variance in two-character word reading compared to single-character reading, suggesting that the cognitive demands of reading two-character words in Chinese differ from those of single-character reading. Additionally, we examined the moderating effect of age on the relationship between EF and word reading. No significant moderating effect was found, indicating a constant contribution of EF to word reading across different age groups among CSL learners. These findings offer valuable theoretical insights into the role of EF in L2 literacy development and suggest practical pedagogical strategies for enhancing word reading skills among CSL learners.